2014
DOI: 10.3109/15376516.2014.886003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetyl-l-cysteine,in vivo, against pathological changes induced by malathion

Abstract: Malathion toxicity has been related to the inhibition of acetylcholinesterase, induction of oxidative stress, liver damage and impairment of kidney function as well as hematotoxicity. N-acetyl-l-cysteine (NAC) has been shown to possess curative effects in experimental and clinical investigations. The present study was designed to evaluate the protective effect of NAC against toxic consequences of malathion exposure in Wistar rats. Malathion was given daily to rats via oral gavage and NAC in drinking water duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…This observation suggests that the more brain-exclusive inflammatory priming we find in our GWI model may be specific to DFP, and other OP exposures. However, OP compounds have been identified to cause liver damage and associated inflammation (Mostafalou et al, 2012; Lasram et al, 2014; Ezzi et al, 2016), supported by the observed increases in IL-6, IL-1b, LIF, and OSM mRNA in the liver and IL-6 and KC levels in the serum, though these responses were generally suppressed by CORT. Our hypothesis is that exposure to DFP directly instigates neuroinflammation that can be primed by CORT, as we have observed no indicators of neuronal damage in these mice (O’Callaghan et al, 2015), while the peripheral cytokine responses are the result of liver damage-induced inflammation that is non-responsive to prior CORT exposure (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…This observation suggests that the more brain-exclusive inflammatory priming we find in our GWI model may be specific to DFP, and other OP exposures. However, OP compounds have been identified to cause liver damage and associated inflammation (Mostafalou et al, 2012; Lasram et al, 2014; Ezzi et al, 2016), supported by the observed increases in IL-6, IL-1b, LIF, and OSM mRNA in the liver and IL-6 and KC levels in the serum, though these responses were generally suppressed by CORT. Our hypothesis is that exposure to DFP directly instigates neuroinflammation that can be primed by CORT, as we have observed no indicators of neuronal damage in these mice (O’Callaghan et al, 2015), while the peripheral cytokine responses are the result of liver damage-induced inflammation that is non-responsive to prior CORT exposure (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…However, liver GSH levels in the current study were increased by NAC administration because of facilitating GSH biosynthesis. Number of researchers suggested that NAC is effective as a chelating agent in reducing the toxicity of pesticide when it administrated on intoxicated animals (Borgstrom et al 1986;Zimet 1988;Lasram et al 2014b). …”
Section: Discussionmentioning
confidence: 99%
“…For instance, insecticide cypermethrin (synthetic pyrethroid) inhibited erythroid and granulocyte-macrophage progenitors in vitro 31 , while low doses of the OP mevinphos caused destruction of progenitors in human and rat hematopoietic progenitor cells 32 . There is also experimental evidence that insecticides malathion (OP) and carbaryl (carbamate) may induce anemia, immunosuppression, and altered number of leukocytes and platelets in vivo 33,34 . It is noteworthy to mention that previous studies have reported elevated risks for lymphatic and hematopoietic neoplasms, including chronic lymphoid leukemia, Hodgkin and non-Hodgkin lymphoma, and multiple myeloma, among farmers 35,36 and workers occupationally exposed to OP insecticides 37 .…”
Section: Pesticide Use and Hematological Parametersmentioning
confidence: 99%